3-D printed primary standards for calibration of microwave network analysers. (1st July 2020) - Jones, Adam; Lucyszyn, Stepan; Márquez-Segura, Enrique; Ridler, Nick; Skinner, James; Stokes, Daniel
Highlights: 3-D printing used to manufacture primary standards for microwave measurements. Printing using polymers; metal-plated to achieve required electrical performance. Performance compares favourably with existing UK national standards. New traceability approach proved: traceability originating at end-user locations. Abstract: This paper describes the design, fabrication and testing of 3-D printed primary standards for use with the calibration of microwave vector network analysers. The standards are a short-circuit and a quarter wavelength section of line that are designed for use with the Thru-Reflect-Line calibration technique. The standards are realised in metal-pipe rectangular waveguide, covering the frequency range from 12 GHz to 18 GHz (i.e., Ku-band). The standards are polymer-based 3-D printed, which is subsequently metal plated to provide the required electrical conductivity. The performance of the standards is compared with conventionally machined standards that are used as part of the UK's primary national measurement system for microwave scattering parameters. The authors believe that this is the first time that 3-D printing techniques have been used to produce such calibration standards, and, that this could lead to a new approach to providing metrological traceability for these types of measurement.